Upaya Pencegahan Perundungan Melalui Sosialisasi Dan Penerapan 3 Magic Words Pada Siswa SDN 1 Bengkulu Selatan - Nadila Septrianti; Muhammad Yusuf Athallah; Natasya Maulina; Trisuci Kurnia Ilahi; Muhammad Akbar Al Faruq; Taufik Hasyim (CV. ITTC INDONESIA, 2026)
Cases of bullying in Indonesia continue to rise each year, with the highest incidence occurring at the elementary school level, a pattern also observed among elementary-aged children in Kelurahan Belakang Gedung, Pasar Manna District, South Bengkulu Regency, who frequently display rude behavior and speech toward peers, raising concern that such behavior may escalate into bullying if left unaddressed. In response, the KKN Team of Bengkulu University Period 108 Group 112 carried out a community service activity,